Urban activism and cosmopolitan aesthetics in times of crisis: “Thessaloniki Otherwise” meets Stuttgart - Deltsou, Eleftheria (The Greek Review of Social Research, 2018)
“Thessaloniki Otherwise” an urban activist group in Thessaloniki, Greece, has been since 2010 disrupting the city’s daily routines by performatively enacting alternative city politics and aesthetics. This article first wonders whether the simultaneity of its establishment with the Greek economic crisis typify its politics as resistance or consent. It then focuses on an event in Stuttgart, Germany, as a performance of place that refuted the economic crisis as also a crisis of national essence. It is argued that this event employed an aesthetic cosmopolitanism, whose rhetorics of creativity, entrepreneurialism and art aimed at countering anti-Greek European views and claiming coeval and coequal participation in hegemonic Europeanness, and opposed both foreign media representations of Greece and classic ancient Greek representations. Finally, the article contemplates over whether such a cosmopolitan locality constitutes a form of crypto-colonialism.